Notes to Philosophy 167: Class 11 -- Other Developments in Astronomy from 1642 to 1684 -- Part 5. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Streete's Astronomia Carolina (1661) -- The Founding of the Royal Society (1660-63); Generally corresponds to the video segment: Class 11, Part 5.